Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/cji.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Modified Protocol of Nivolumab in Relapsed/Refractory Hodgkin Lymphoma: A Brief Communication of Real World Data

Abstract: Immune check point inhibitors such as nivolumab are changing the treatment paradigm of relapsed/refractory Hodgkin lymphoma (r/rHL). Data from single arm studies have shown nivolumab to be an effective and safe therapy. Real world data from resource constrained settings are limited. Our study is a retrospective single center analysis of nivolumab in r/rHL from India. Data regarding baseline and pretreatment characteristics were collected for 20 patients treated with nivolumab from January 2016 to March 2021. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Growing evidence supports its administration as a second or first-line drug in newly diagnosed HL [ 15 ]. In a recent retrospective study, nivolumab showed comparable safety and efficacy in treating patients with refractory HL [ 16 ]. However, it is known for its various immune-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports its administration as a second or first-line drug in newly diagnosed HL [ 15 ]. In a recent retrospective study, nivolumab showed comparable safety and efficacy in treating patients with refractory HL [ 16 ]. However, it is known for its various immune-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a small subset of patients who had finished two years of therapy and were then monitored but continued to progress could undergo retreatment. Another more recent research showed that nivolumab is a viable and effective treatment for relapsed/refractory Hodgkin lymphoma (r/rHL) [8]. A remarkable 90% of patients responded to nivolumab therapy overall, with 40% experiencing complete remission after it was stopped.…”
Section: Nivolumabmentioning
confidence: 99%